IMPLEMENTASI NILAI ANTI KORUPSI DENGAN PROJECT CITIZEN PADA MATA KULIAH PENDIDIKAN KEWARGANEGARAAN - Rohani, Rohani; Firmansyah, Syarif (Universitas Muria Kudus, 2023)
The aim of this research is to implement anti-corruption values to students using the project citizen model.The research method used is descriptive qualitative. Data collection techniques in thisresearch, researchers used data collection techniques in the form of observation, interviews, documentation, triangulation and literature study. The analysis techniques used are data reduction, data presentation, and drawing conclusions/verification.The results of the research show that the implementation of anti-corruption education at IKIP PGRI Pontianak is a mandatory subject for the Civics Study Program and is integrated with Civics courses in other study programs, apart from that it is also implemented through student activities, extracurricular activities, and study program association activities and student unit activities. . The steps in the project citizen model are identifying problems, selecting problems, collecting information related to the problem, developing a class portfolio, presenting the class portfolio and reflecting on learning experiences. The anti-corruption values implemented through the project citizen learning model consist of honesty, discipline, hard work, caring, courage, responsibility, simplicity, independence and justice.